As an introduction to the dossier "Cosmopolitics and Emancipation in Latin America" - Rueda Barrera, Eduardo A. (2024)
After exploring the practical-political meaning that underlies the idea of ??“cosmopolitics” and describing its impact on the transformative agendas of Latin America, its links with cosmopolitanism are explained. At the end, the work of the Dossier is briefly reviewed.